Management intrazerebraler Blutungen: lernen wir dazu? - Staykov, Dimitre; Köhrmann, Martin; Unterberg, Andreas (Der Nervenarzt, 2012)
Summary: Intracerebral hemorrhage (ICH) is the most devastating form of stroke. It affects approximately 2 million people worldwide every year and is a major cause of mortality and morbidity. Despite the focus of intensive scientific research on ICH for decades there is still no proven treatment strategy for this disease. Advances in knowledge on the underlying pathomechanisms of ICH and the clinical impact have contributed to the development of novel treatment approaches. Currently, surgical treatment, aggressive blood pressure management and intraventricular fibrinolysis in patients with additional severe intraventricular hemorrhage are being investigated in large scale phase III clinical trials.